2022
DOI: 10.3389/fpls.2022.875824
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Multiple Species Invasion on Soil and Plant Communities Increases With Invasive Species Co-occurrence

Abstract: Despite increasing evidence indicating that invasive species are harming biodiversity, ecological systems and processes, impacts of multiple species invasion and their links with changes in plant and soil communities are inadequately documented and remain poorly understood. Addressing multiple invaders would help to ward against community-wide, synergistic effects, aiding in designing more effective control strategies. In this work, correlative relationships are examined for potential impacts of three co-occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Research on the community-level consequences and management of multispecies plant invasion is growing (e.g. [ 26 , 36 , 44 ]), and more studies of mixed-species animal communities have been called for [ 41 ]. In practice, information on the structure and function of mixed species communities serves a different and complementary purpose to understanding the ecological processes outlined above.…”
Section: The Ecology Of Mixed Species Landscapes Under a Nature-posit...mentioning
confidence: 99%
See 1 more Smart Citation
“…Research on the community-level consequences and management of multispecies plant invasion is growing (e.g. [ 26 , 36 , 44 ]), and more studies of mixed-species animal communities have been called for [ 41 ]. In practice, information on the structure and function of mixed species communities serves a different and complementary purpose to understanding the ecological processes outlined above.…”
Section: The Ecology Of Mixed Species Landscapes Under a Nature-posit...mentioning
confidence: 99%
“…For example, alien species in mixed-species animal communities can have superior performance for several traits compared to native community members (such as growth rates, physiological tolerance or higher fecundity), although such animal community-level studies are rare [ 41 ]. In general, introduced and native plants are phylogenetically similar and their traits are functionally distinct when contrasted with co-occurring natives [ 58 ], although at local, in situ community to landscape scales, these patterns can vary and be scale-dependent [ 44 ]. In plant communities, community-wide traits such as seed mass, specific leaf area and herbivore resistance have been shown to be correlated with invasion success at particular spatial scales and points of time in the invasion process [ 21 , 59 ].…”
Section: The Ecology Of Mixed Species Landscapes Under a Nature-posit...mentioning
confidence: 99%
“…Invasive plant species can outcompete and reduce the abundance of native plant species [ 42 ], alter soil properties [ 26 ], and homogenize the biodiversity of invaded communities and ecosystems [ 43 ]. Invasive plant species may alter soil properties in their new ranges, but the magnitude and direction of these changes are sometimes unique to each invasive species and often vary among habitats for the same non-native species [ 6 , 8 , 12 , 32 , 33 , 44 , 45 ]. To the best of our knowledge, this is the first study to investigate the biogeochemical consequences of the invasion of Prosopis juliflora , Ipomoea carnea , Leucaena leucocephala , and Opuntia ficus-indica in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported no statistically significant difference among the properties and microelements of soils from habitats infested with invasive plant species compared to the soils of equivalent habitats occupied by native plant species [ 6 , 8 , 12 , 32 , 33 ]. Moreover, several studies that have compared the capacity of multiple invasive species to alter soil properties within the same experiments design have revealed contrasting results among the species examined [ 6 , 8 , 32 ]. Other studies have reported that the same invasive species alters soil dynamics in different ways in different habitats (communities) or under different experimental conditions [ 6 , 8 , 12 ].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation